PENGARUH MEDIA PHYSIC EDUCATIONAL TECNOLOGY (PhET) TERHADAP HASIL BELAJAR SISWA PADA MATERI BENTUK MOLEKUL - Rian Atmawinaldi; Andi Ifriany Harun; Rody Putra Sartika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThis research is backed by low student learning outcomes. This research aims to determine: 1) The difference of learning outcomes of grade X class MIA SMA Bina Utama Pontianak who use the media simulation Physic Educational Tecnology (PhET) and students who do not use the PhET simulation media on materials molecular shape, 2) determine the influence of the use of the PhET simulation media to study outcomes on the subject of chemical materials molecular shape grade X class MIA SMA Bina Utama. Samples are selected based on the saturated sample technique. The form of research in use is (Quasi experimental design) by designing the research used is "Nonequivalent control group Design". The data collection tools used are test learning results. Based on the analysis of posttest data using Test T obtained the value of Sig (2-tailed) by 0.000. This shows that there is a difference in learning outcomes between students who are taught using the PhET simulation media and students who are tutored without using the PhET simulation media. Learning to use the PhET simulation media on the molecular material in SMA Bina Utama Pontianak has influenced the effect size of 2.45 on the increase of student learning outcomes. Keywords: Learning Outcomes, Molecular Shapes, Physic Educational Tecnology (PhET)